South Africa's Achilles' Heel and Phoenixian Possibilities - Nkomo, Mokubung (South African Journal of Higher Education, 2016)
South Africa’s education system is perched on a slippery and dangerous slope. The choice is either to stay mired in a state of stagnation, embellished by a beguiling new vocabulary of change, or to turn a crippling legacy through an authentically transformed vision, fueled by a trenchant and sustained vigour. The thrust of the article is on the tertiary sector, although, in an attempt to provide a backdrop, reference is made to the historical inadequacies of general, pre-university education to explain the enduring effects of the design that has nurtured a debilitating underdevelopment that bedevils the present. The article reflects on the heavy weight of an inheritance that is transmitted intergenerationally and differentiated through racialized and gendered epistemologies, pedagogies, and curricula; all these are deeply embedded in institutional cultures that are routinely executed by a formidable staff complement socialized with dated attitudes and practices. My reflections are largely informed by the report of the 2008 Ministerial Committee on the Transformation and Social Cohesion and the Elimination of Discrimination in Public Higher Education Institution (MCHET). Through the identification of new emergent trends I ponder on the possibilities that could lead to a meaningful and inclusive transformation, with benefits accruing to all and not only to small segments of South African society.